Influence of the Oil Phase and Topical Formulation on the Wound Healing Ability of a Birch Bark Dry Extract. - Isabel Steinbrenner; Pia Houdek; Simone Pollok; Johanna M Brandner; Rolf Daniels (PLoS ONE, 2016)
Triterpenes from the outer bark of birch are known for various pharmacological effects including enhanced wound healing (WH). A birch bark dry extract (TE) obtained by accelerated solvent extraction showed the ability to form oleogels when it is suspended in oils. Consistency of the oleogels and the dissolved amount of triterpenes varies largely with the used oil. Here we wanted to know to what extent different oils and formulations (oleogel versus o/w emulsion) influence WH. Looking at the plain oils, medium-chain triglycerides (MCT) enhanced WH (ca. 1.4-fold), while e.g. castor oil (ca.0.3-fold) or light liquid paraffin (LLP; ca. 0.5-fold) significantly decreased WH. Concerning the respective oleogels, TE-MCT showed no improvement although the solubility of the TE was high. In contrast, the oleogel of sunflower oil which alone showed a slight tendency to impair WH, enhanced WH significantly (ca. 1.6-fold). These results can be explained by release experiments where the release rate of betulin, the main component of TE, from MCT oleogels was significantly lower than from sunflower oil oleogels. LLP impaired WH as plain oil and even though it released betulin comparable to sunflower oil it still results in an overall negative effect of the oleogel on WH. As a further formulation option also surfactant free o/w emulsions were prepared using MCT, sunflower oil and LLP as a nonpolar oil phase. Depending on the preparation method (suspension or oleogel method) the distribution of the TE varied markedly and affected also release kinetics. However, the released betulin was clearly below the values measured with the respective oleogels. Consequently, none of the emulsions showed a significantly positive effect on WH. In conclusion, our data show that the oil used as a vehicle influences wound healing not only by affecting the release of the extract, but also by having its own vehicle effect on wound healing. This is also of importance for other applications where drugs have to be applied in non-polar vehicles because these solvents likely influence the outcome of the experiment substantially.